Research on Telecom Data Service Open Ability Under the Environment of Big Data - Chun Liu; Haifeng Zou; Yong Xiang (Dianxin kexue)
Data resource is the core asset of telecom operators, under the environment of the data surging, opening data service ability is advantage to the operator to increase the value and revenue of pipeline, but it also need higher requirements of the operating capacity. On the basis of researching the requirements of data service ability open business under the environment of big data, the data service content was clearly introduced, the construction ideas, system architecture and open mechanism of the data service ability open platform were put forward.